Jihadi Attacks, Media and Local Hate Crime - Ria Ivandic; Tom Kirchmaier; Stephen Machin (Institute of Labor Economics (IZA), 2019)
Empirical connections between local anti-Muslim hate crimes and international jihadi terror attacks are studied. Based upon rich administrative data from Greater Manchester Police, event studies of ten terror attacks reveal an immediate big spike up in Islamophobic hate crimes and incidents when an attack occurs. In subsequent days, hate crime is amplified by real-time media. It subsequently attenuates, but hate crime incidence cumulates to higher levels than prior to the series of attacks. The overall conclusion is that, even when they reside in places far away from where jihadi terror attacks take place, local Muslim populations face a media magnified likelihood of hate crime victimization following international terror attacks. This matters for community cohesion in places affected by discriminatory hate crime and, from both a policy and research perspective, means that the process of media magnification of hate crime needs to be better understood.
Keywords: K42; 330; islamophobic hate crime; Jihadi terror attacks; media